Fraud Triangle Theory on Accounting Students Online Academic Cheating - Indriyana Puspitosari (Accounting and Finance Studies, 2022)
Academic cheating is a phenomenon found in the academic area. Cheating, copying answers, plagiarism are some forms of academic cheating. Online learning that has been carried out during the pandemic is also not free from the phenomenon of cheating. This study aims to see the effect of the Fraud triangle theory dimension on online academic cheating behavior in accounting students. The data of this study were obtained from questionnaire data distributed to accounting students at UIN Raden Mas Said Surakarta. The respondents of this study amounted to 203 people. The analysis technique is carried out using multiple linear analysis The results of this study indicate that there are two dimensions of the fraud triangle that can increase online academic cheating behavior in students, namely opportunity and pressure. This research is expected to help the education system in universities to understand how severe the problem of online cheating is among students, but they can also help universities in identifying the underlying motives behind cheating behavior.